Pigeons as Carriers of Clinically Relevant Multidrug-Resistant Pathogens—A Clinical Case Report and Literature Review - Chrobak-Chmiel, Dorota; Kwiecień, Ewelina; Golke, Anna; Dolka, Beata; Adamczyk, Krzysztof; Biegańska, Małgorzata J.; Spinu, Marina; Binek, Marian; Rzewuska, Magdalena (Frontiers in Veterinary Science, 2021)
Pigeons are widespread bird species in urban regions (Columba livia forma urbana) and may carry pathogens with zoonotic potential. In recent years, more and more data indicate that these zoonotic pathogens are multidrug resistant. Our results confirmed that global trend. Three different multidrug-resistant pathogens were isolated from an oral cavity of a racing pigeon with lesions typical for pigeon pox virus infection. Staphylococcus aureus was recognized as methicillin resistant, thus resistant to all beta-lactams. Additionally, it was also resistant to many other classes of antibiotics, namely: aminoglycosides, tetracyclines, phenicols, lincosamides, and macrolides. Escherichia coli showed resistance to all antimicrobials tested, and it was classified as intermediate to amikacin. Moreover, Candida albicans resistant to clotrimazole, natamycin, flucytosine, and amphotericin and intermediate to ketoconazole, nystatin, and econazole was also isolated. This raises the question how pigeons acquire such highly resistant strains. Therefore, more data are needed concerning the resistance to antibiotics in strains from domestic and wild pigeons in Poland. Until the problem is fully understood, it will be challenging to implement adequate planning of any control measures and check their effectiveness.